2017
DOI: 10.1002/ijc.30608
|View full text |Cite
|
Sign up to set email alerts
|

Geographic heterogeneity in the prevalence of human papillomavirus in head and neck cancer

Abstract: Human papillomavirus (HPV) causes oropharyngeal squamous cell carcinoma (OPSCC), although strongly divergent results have been reported regarding the prevalence of HPV16 in different countries, whether this represents important differences in etiology remains unclear. Applying rigorous protocols for sample processing, we centrally evaluated 1,420 head and neck tumors (533 oropharynx, 395 oral cavity and 482 larynx) from studies conducted in the US, Europe and Brazil for mucosal HPV DNA and p16 expression to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
2
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(140 citation statements)
references
References 36 publications
6
124
2
8
Order By: Relevance
“…This analysis is based on cases derived from case-control studies of HNSCCs in three distinct regions[15]. Studies included: the Brazilian Head and Neck Genome Project (GENCAPO; Southern Brazil – São Paulo)[16], the Carolina Head and Neck Cancer Study (CHANCE, North Carolina, U.S.A.)[17] and the Alcohol Related Cancers and Genetic Susceptibility in Europe study (ARCAGE).…”
Section: Methodsmentioning
confidence: 99%
“…This analysis is based on cases derived from case-control studies of HNSCCs in three distinct regions[15]. Studies included: the Brazilian Head and Neck Genome Project (GENCAPO; Southern Brazil – São Paulo)[16], the Carolina Head and Neck Cancer Study (CHANCE, North Carolina, U.S.A.)[17] and the Alcohol Related Cancers and Genetic Susceptibility in Europe study (ARCAGE).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the prevalence of HPV seems to differ due to geographically different exposure. This phenomenon was analysed by Anantharam et al The authors could show a higher prevalence rate of HPV in the US and a missing prevalence in South America in non-oropharyngeal SCC [13]. …”
Section: Discussionmentioning
confidence: 99%
“…The different HPV types are characterized by variations in the DNA sequences of L1 and divided into high-and low-risk types [15]. High-risk types include HPV- 16,18,31,32,33,35,39,45,51,52,56,58,59,66, and 68, and low-risk types are HPV-6, 11, 42, 43, and 44. The high-risk HPV (HR-HPV) types 16 and 18 are the most common etiological agents in 70% of cervical cancers globally.…”
Section: Hpv Biologymentioning
confidence: 99%
“…The prevalence of HR-HPV in cancers of the oral cavity shows high variability [39]. We have included 50 oral cancer studies reported during 2007-2017, comprising a total of 6,349 samples and individual studies comprising a minimum of 30 oral cancer samples.…”
Section: Hpv Prevalence In Oral Cancermentioning
confidence: 99%